Protected areas, tourism economy and employment generation: A case study from India - Sharma, Shweta; Sood, Shamli; Chaudhry, Pradeep (Ecological Questions, 2019)
Wildlife tourism in the form of Tiger Tourism dominates in India as the country is home to more than half of the world’s tiger population. The first tiger reserve was established in India in 1973.At present, there are 50 tiger reserves in the country, which are administered by the National Tiger Conservation Authority (NTCA) at the central level and state forest & wildlife departments at the field level. The present case study concerns the assessment of tourism economy and employment generation in one of the prominent tiger reserves in India, i.e. the Satpura Tiger Reserve of the Madhya Pradesh state. Based on the primary and secondary data, it has been estimated that the expenditure incurred by tourists in the Satpura Tiger Reserve between 2017 and 2018 amounted to INR 1,110 million (equivalent to USD 15,416,666; 1 USD = 72 INR). At the same time, around 127,187 man-days were generated for the nearby local community from the tourism establishments.